Phenotypic characterization of sheep populations in Tahtay Maichew district, Northern Ethiopia - Abebe Hailu; Amine Mustefa; Tesfalem Asegede; Abraham Assefa; Seble Sinkie; Semere Tsewene (Genetic Resources, 2020)
Eighteen quantitative measurements and fourteen qualitative characteristics taken from 306 adult sheep (57 rams and 249 ewes) were used to characterize sheep populations of district, Ethiopia. Most traits showed significant variation by zone, sex and age groups with higher values generally recorded for rams as compared to ewes. Middle age group animals displayed highest values for several traits, reflecting the optimal production age. zone affected ewes more than rams. The highland sheep height at withers, widest shoulder points and longest hair, indicative of adaptation to their environment. Qualitative characteristics of the studied sheep populations such as tail shape, plain coat color pattern, skin, hairy fiber and the absence of horn, toggle, ruff and beard suggest that they constitute a previously sheep breed. Tan coat color differentiated high and midland sheep from lowland sheep where white and brown colors were dominant. Canon bone length, height at withers and tail length were the three most important variables used in discriminating the sheep populations. On average 66% of the animals could be classified into their respective zone. Our data suggest that highland sheep populations are distantly related to lowland sheep, while midland sheep are more closely related to lowland sheep. It can be concluded that breeding programs specific to each zone need to be designed for sustainable utilization and conservation of the studied sheep populations. Furthermore, molecular based studies might allow further characterization of Ethiopian sheep breeds.